2016
DOI: 10.1159/000441273
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Cystatin-C Levels Correlate with Reduced Renal Volumes in Neonates with Intrauterine Growth Restriction

Abstract: Background: Exposure to intrauterine growth retardation (IUGR) can have a negative impact on nephrogenesis resulting in limited fetal kidney development and supporting the hypothesis that IUGR represents a risk for renal function and long-term renal disease. Cystatin-C (Cys-C), a strong inhibitor of cysteine proteinases, is freely filtered by the kidney glomerulus and is reabsorbed by the tubules, where it is almost totally catabolized; what remains is subsequently eliminated in urine. In tubular diseases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…FGR infants born preterm also have an increased risk of retinopathy of prematurity (57). FGR is linked to altered nephrogenesis, due to suboptimal tubular development caused by intrauterine hypoxia (58), and in turn, urinary Cystatin-C excretion is increased in FGR infants compared to appropriately-grown infants which is seen to reflect reduced renal volume (59). It is therefore suggested that increased secretion of Cystatin-C signifies nephron loss as a result of the negative impact of FGR on kidney development.…”
Section: Perinatal Morbiditiesmentioning
confidence: 99%
“…FGR infants born preterm also have an increased risk of retinopathy of prematurity (57). FGR is linked to altered nephrogenesis, due to suboptimal tubular development caused by intrauterine hypoxia (58), and in turn, urinary Cystatin-C excretion is increased in FGR infants compared to appropriately-grown infants which is seen to reflect reduced renal volume (59). It is therefore suggested that increased secretion of Cystatin-C signifies nephron loss as a result of the negative impact of FGR on kidney development.…”
Section: Perinatal Morbiditiesmentioning
confidence: 99%
“…Barbati et al . reported that IUGR newborns had a statistically significant elevation of urinary Cys‐C, inversely correlated with whole renal/renal cortex volume . In proximal tubules, filtered Cys‐C is reabsorbed by megalin‐facilitated endocytosis, and its increased urinary elimination in IUGR children could be indicative of reduced degradation and reabsorption .…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Barbati et al reported that IUGR newborns had a statistically significant elevation of urinary Cys-C, inversely correlated with whole renal/renal cortex volume. 19 In proximal tubules, filtered Cys-C is reabsorbed by megalinfacilitated endocytosis, and its increased urinary elimination in IUGR children could be indicative of reduced degradation and reabsorption. 15 In the present study, both b2-MG and Cys-C were elevated at 4 and 8 weeks of age, and, taking into account these previous reports, it can be said that due to the immature reabsorption function of the renal tubule, they flowed into urine.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported high levels of cystatin C, a marker of renal function, in LBW children (Franco et al, 2008b). Additionally, Barbati et al (2016) have shown high levels of cystatin C in urine of LBW neonates. These authors observed an inverse correlation between cystatin C levels and renal volume (Barbati et al, 2016).…”
Section: Kidney Disease and Barker Hypothesis: Importance Of Fetal Enmentioning
confidence: 95%
“…Additionally, Barbati et al (2016) have shown high levels of cystatin C in urine of LBW neonates. These authors observed an inverse correlation between cystatin C levels and renal volume (Barbati et al, 2016).…”
Section: Kidney Disease and Barker Hypothesis: Importance Of Fetal Enmentioning
confidence: 99%